Parochial political culture and the squabbles for national agenda setting in Nigeria: A theoretical overview - Abbo, Usman; Bashir, Adamu (2020)
The setting of agenda is the first and critical step in the policy cycle, outlining key issues that attract government attention. Which has a vital impact on their policy process 's entire trajectory. Activities in this initial phase will decide if the government can fix a problem or abandon it at a later point. However, in Nigeria the type of political culture practiced has invariably accounted for lack of interest and commitment on the part of the people to setting national agenda. This is because Nigeria is one of the world's most divided nations, with a very sharp dichotomy primarily along religious and ethnic lines that overlap. These lines of demarcations continue to form and influence political action in the country where most Nigerians think of themselves as Nigerians in some way, but their ethnic identity matters more as a source of pride and more importantly as a source of government policy likes and dislikes. This paper argued that Nigerians' lack of emotional attachment to the national agenda has denied the country a sustainable national development. The leaders capitalize on the parochial attitudes of the citizen toward national agenda to deny the country a systemic and sustainable development where instead of pursuing development policy goals they are busy amassing wealth for their personal benefit, and this accounts for the high level of corruption, ineptitude and lack of political direction that has hindered the growth and development of the country. With over reliance on secondary data obtained through content analysis the paper argues that in order to achieve Nigeria’s developmental objectives there is a strong need for a deep mental change among the citizens so as to do away with vices such as ethnicity and regionalism that are currently taken a toll on the country’s drive toward maturity.